Optimal inventory control in a multi-period newsvendor problem with non-stationary demand. Issue 1 (January 2015) - Kim, Gitae; Wu, Kan; Huang, Edward
Abstract The optimal control of inventory in supply chains plays a key role in the competiveness of a corporation. The inventory cost can account for half of company's logistics cost. The classical inventory models, e.g., newsvendor and EOQ models, assume either a single or infinite planning periods. However, these models may not be applied to perishable products which usually have a certain shelf life. To optimize the total logistic cost for perishable products, this paper presents a multi-period newsvendor model, and the problem is formulated as a multi-stage stochastic programming model with integer recourse decisions. We extend the progressive hedging method to solve the model efficiently. A numerical example and its sensitivity analysis are demonstrated.